2016
DOI: 10.5713/ajas.16.0353
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diet on the composition and relative abundance of rumen microbes in goat

Abstract: ObjectiveThis experiment was conducted to explore the impact of diet on the ruminal microbial community in goats.MethodsTwelve goats were divided into two groups and fed complete feed (CF) or all forage (AF) diet. The total microbial DNAs in the rumen liquid were extracted. The V4 region of microbial 16S rRNA genes was amplified and sequenced using high-throughput. Information of sequences was mainly analyzed by QIIME 1.8.0.ResultsThe results showed that Bacteroidetes and Firmicutes were the most predominant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 30 publications
5
40
0
2
Order By: Relevance
“…Firmicutes and Bacteroidetes, it still plays an important role in the formation and fermentation of biofilms and the digestion of soluble carbohydrates (Pitta et al 2016). In addition, it was reported that Proteobacteria had the highest abundance in the rumen of goat fed with complete feed (higher protein content while lower neutral detergent fiber and acid detergent fiber contents) than fed with all forage diet (Liu et al 2017). In the existing research, the soluble carbohydrates and protein contents were higher while neutral detergent fiber and acid detergent fiber contents were substantially lower in oat hay-diet than that in native pasture-diet.…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes and Bacteroidetes, it still plays an important role in the formation and fermentation of biofilms and the digestion of soluble carbohydrates (Pitta et al 2016). In addition, it was reported that Proteobacteria had the highest abundance in the rumen of goat fed with complete feed (higher protein content while lower neutral detergent fiber and acid detergent fiber contents) than fed with all forage diet (Liu et al 2017). In the existing research, the soluble carbohydrates and protein contents were higher while neutral detergent fiber and acid detergent fiber contents were substantially lower in oat hay-diet than that in native pasture-diet.…”
Section: Discussionmentioning
confidence: 99%
“…The members of Proteobacteria were lower in G2 and G3 camels that were fed on diet rich in fiber contents. These findings highlighted this phylum's function as a protein-degrading bacteria (Liu et al, 2017). The abundance of Treponema was higher in the solid fraction and in G3 camels (Figure 1a).…”
Section: Bacterial Communitymentioning
confidence: 69%
“…We identified two unique species from Tenericutes and Spirochaetae that contributed to distinguishing the OG group from the other two groups. Tenericutes has been identified in regions with various kinds of grass orchards worldwide (Liu et al, 2017;Deakin et al, 2018). Spirochaetae has also been identified in regions planted with grass orchards (Brown, 1943).…”
Section: Effect Of Companion Planting On Soil Bacteria Community Strumentioning
confidence: 99%